2011
DOI: 10.4028/www.scientific.net/amm.138-139.1221
|View full text |Cite
|
Sign up to set email alerts
|

Advances on the Pharmacology Research of Active Component in Humic Acid

Abstract: The humic acids in young coal are complex compounds of aromatic-fatty group organic acid with content of functional groups like carboxy, phenolic hydroxyl group, benzoquinonyl, alcohol group , ketone group etc. The pharmacology research of humic acid advanced in slow progress as a result of composition complexity and raw material multiplicity. At first it was analysed that terpene, steroids and other bioactive substances existed in natural humic having effects on antibacterial, antiviral, antitumor and microci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Fulvic acid (FA) is a component of humic acid (HA) with low aromaticity, small molecules, many functional groups, and good water solubility. It has the highest chemical, physiological, and physicochemical activities of all the components of HA. FA has several desirable characteristics: it functions as a platform compound, is easy to combine or react with other substances, has micro- to nanometer size and good biocompatibility. , Recent studies have shown that FA plays a special role in the prevention and control of human and animal diseases, heavy metal pollution control in water and soil, ,, modern agriculture, ,,− and other fields. The potential biochemical activities of FA have attracted the research interest of many scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Fulvic acid (FA) is a component of humic acid (HA) with low aromaticity, small molecules, many functional groups, and good water solubility. It has the highest chemical, physiological, and physicochemical activities of all the components of HA. FA has several desirable characteristics: it functions as a platform compound, is easy to combine or react with other substances, has micro- to nanometer size and good biocompatibility. , Recent studies have shown that FA plays a special role in the prevention and control of human and animal diseases, heavy metal pollution control in water and soil, ,, modern agriculture, ,,− and other fields. The potential biochemical activities of FA have attracted the research interest of many scholars.…”
Section: Introductionmentioning
confidence: 99%